Pengaruh Keberhasilan Penerapan Sistem PPUBU (Pekerja Penerima Upah Badan Usaha) dan PBPU (Pekerja Bukan Penerima Upah) dalam Sistem Layanan Kesehatan - Satrio Novianto; Renny Oktafia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to examine the influence of the successful implementation of the PPUBU (Business Entity Wage Receiving Workers) and PBPU (Non-Wage Receiving Workers) systems in the health service system. This system is relevant because of the important role of workers in supporting the continuity of health services in various business entities. The research method used is a descriptive and quantitative analysis approach involving participants from workers who are members of the PPUBU and PBPU systems in the health sector. Data collection was carried out through surveys, interviews and observations, with a focus on critical aspects of successful system implementation.The research results show that the successful implementation of the PPUBU and PBPU systems has a positive effect on the quality of health services. Factors such as workers' understanding of the system, management support, and integration of the system with daily work processes play a crucial role in increasing the effectiveness of health services